2015
DOI: 10.1016/j.bpj.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Biomolecular Force Fields for Simulations of Polyglutamine in Solution

Abstract: Polyglutamine (polyQ) peptides are a useful model system for biophysical studies of protein folding and aggregation, both for their intriguing aggregation properties and their own relevance to human disease. The genetic expansion of a polyQ tract triggers the formation of amyloid aggregates associated with nine neurodegenerative diseases. Several clearly identifiable and separable factors, notably the length of the polyQ tract, influence the mechanism of aggregation, its associated kinetics, and the ensemble o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 102 publications
1
45
0
Order By: Relevance
“…[23][24][25]27,28,42,[44][45][46] On the other hand, the accuracy of unfolded state and IDP structural ensembles obtained using several widely-used force fields has been called into question. [25][26][27]43,[46][47][48][49][50][51][52][53] Piana et al suggested that modern force fields, including Amber ff99sb*-ildn and CHARMM 22* in particular, produce IDP and unfolded state ensembles that are on average too compact. 48 It has also been suggested that Amber force fields systematically underestimate chain dimensions of IDPs and unfolded states.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25]27,28,42,[44][45][46] On the other hand, the accuracy of unfolded state and IDP structural ensembles obtained using several widely-used force fields has been called into question. [25][26][27]43,[46][47][48][49][50][51][52][53] Piana et al suggested that modern force fields, including Amber ff99sb*-ildn and CHARMM 22* in particular, produce IDP and unfolded state ensembles that are on average too compact. 48 It has also been suggested that Amber force fields systematically underestimate chain dimensions of IDPs and unfolded states.…”
Section: Introductionmentioning
confidence: 99%
“…To directly compare to previous C36 results, 11 we tested C36m by simulating polyglutamine (polyQ) peptide, an IDP with relatively compact collapsed states due to the hydrogen bonding interactions between polar side chains. Similar to the C36 results, the 30-residue polyQ peptide (Q 30 ) was disordered during 98% of the simulation time.…”
mentioning
confidence: 99%
“…In addition, the simulated conformations of Aβ42 peptide are also largely disturbed due to the different force fields, either implicit or explicit solvent model and distinct conditions employed. For example, previous studies had confirmed that Amber and Charmm force fields always over‐stabilize the helical structure and the Gromos ones tend to form β‐structure . Extended simulation for both systems can unify some secondary structure components but all.…”
Section: Resultsmentioning
confidence: 85%